Types and abundance of phytoplankton in the Parit Belanda River Rumbai Pesisir District, Pekanbaru, Riau - Satria Yunda; Asmika H. Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Phytoplankton is a microscopic aquatic organisms that has limited movement. A research aims to determine types and abundance of phytoplankton has been carried out on December 2016 in the Parit Belanda River. There are three stations namely Station 1 (in the upstream), Station 2 (in the middle) and Station 3 (in the downstream). Samplings were conducted once/week for 4 weeks period. Water quality parameter measured were temperature, transparency, pH, DO, CO2, nitrate and phosphate. Phytoplankton was identified. Result shown that there are 53 types of phytoplankton and they are belonged to 7 classes, namely Bacillariophyceae (17 species), Chlorophyceae (18 species), Cyanophyceae (9 species), Cryptophyceae (1 species), Crysophyceae (1 species) Dinophyceae (3 species), and Xanthophyceae (2 species). Phytoplankton abundance in the Parit Belanda River range from 1,836 – 2,675 cells/L. Water quality parameters were as follows: temperature 28.25-29 oC, transparency 34.4-46.25 cm, pH 5-6, DO 1.95-4.42 mg/L, CO2 32.96-54.95 mg/L, nitrate 0.076-0.137 mg/L, and phosphate 0.194-0.264 mg/L. Based on the abundance of pyhtoplankton, the Parit Belanda River can be categorized as oligotrofic.Keywords:Parit Belanda River, Pyhtoplankton, Oligotrofic, Riau, Water quality.